Modeling Complex Seasonal Avian Migration: Predictions From the Thermal Environment and Resource Availability - Snell, Katherine R. S.; Thorup, Kasper (Frontiers in Ecology and Evolution, 2022)
Billions of birds undertake long-distance migration and the complexity of schedules has only recently become clear. Such movements occur as a response to seasonality but the ultimate drivers of these changing distributions remain difficult to study directly. Modeling seasonal distributions based fundamentally on climate and vegetation without parameterizing with empirical data, we focus on the potential role of ambient temperature and available resources. We simulate the complete annual cycle over the Afro-Palearctic region in a round-trip migration model allowing full variation in the extent and timing of movement, and multiple stopovers. The resultant simulated tracks and associated environmental metrics are interrogated: we evaluate the thermal and resource consequences of staying in Europe versus crossing the Sahara, and secondly identify the movement patterns optimizing exposure to green vegetation and local surpluses. There is a distinct thermal gain from crossing the Sahara and the pattern emerging of optimal seasonal vegetation resemble contemporary migration routes regarding Sahara crossing, loop structure and itinerancy. Thus, our first-principle simulations suggest that variations in migration patterns among species are caused by a complex trade-off between risks and rewards of staying versus moving, including innate physiological constraints and the resultant gain of the high-risk Sahara crossing.